What does in accordance with the Constitution mean? Reflections based on ethics and Kantian policy - Chavez Rabanal, Mario Gonzalo (2022)
In the following lines we reflect on the question, «What does in accordance with the Constitution mean?», first, in terms of the relationship between legal provisions in the context of constitutional supremacy and, secondly, in terms of the constitutional interpretation considering the emblematic case of Marbury vs. Madison, which integrates the interpretation according to the Constitution and finally we analyze what in accordance with the Constitutional means on reflections related to ethics and Kantian policy with emphasis on liberty.